EVALUATION OF EMRAH YUCEL’S FIVE MINARETS IN NEW YORK AND KILL BILL MOVIE POSTERS IN TERMS OF SEMIOTICS - Bülent POLAT (Fırat University, 2019)
Movies come to the forefront as not only art but also an entertainment sector. The marketing step of this sector goes through rather various processes. The commercial steps to which a production is subjected during the periods of pre-production, post-production and reaching to the audience should be investigated one by one. If a production is aimed to reach large masses, elements of advertisement cannot be disregarded. With a sound marketing strategy, the production displays an expansion not only in a certain region but also in a large area, which is a significant element of the profit mechanism. Additionally, certain strategies are devised in the advertisement department for the marketing of the production. On digital platforms, elements, such as posters and brochures, created for publishing in visually printed publications are vital steps aimed at attracting the audience. The place of posters in especially Hollywood movie sector is indisputable. Posters both market the production itself and have a characteristic to spread the production to large masses. Considering the movie history of Hollywood, the significance of posters cannot be confined to merely the aesthetic position in the visual perception. The commercial significance of the posters is a profit-oriented investment for the concerned production companies. In this commercial platform, the works of Emrah Yücel, who is one of the most important figures in poster design, are of utmost significance. In today’s world where poster art creates a perceptual selectivity, Emrah Yücel’s distinctive designs are worth evaluating semiologically. In this study, movie posters of Five Minarets in New York and Kill Bill, which were designed by Emrah Yücel, were evaluated in terms of semiotics and the perception they created on the society along with their awareness in terms of art and commerce were discussed.